Synthesis of Biodiesel in Low-Grade Palm Oil using Geopolymer-ZnO Catalyst - Nabila, Yaasinta Lafasha; usman, Thamrin; Alimuddin, Andi Hairil (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
This study aimed to synthesize biodiesel (fatty acid methyl ester) from low-grade palm oil using geopolymer-ZnO catalyst. The activity of catalyst was tested by mixing low-grade palm oil and methanol in a mole ratio of 1:10, with varying catalyst concentrations of 1%, 3%, and 5% at a temperature of 67 o C and different time intervals. Subsequently, the progression of the reaction was monitored using thin-layer chromatography (TLC). The results showed that catalyst ratios of 1:0, 1:1, and 1:2 provided complete conversion at concentrations of 3% and 5%. Geopolymer-ZnO catalyst reuse test was carried out using a concentration of 5%, followed by washing with n-hexane. After drying at 100 o C, the sample was reused in biodiesel synthesis. The reuse test findings showed optimum results at 1:2 variation and 2 hours of reaction time with total methyl ester conversion. In addition, the majority of the experiments performed were carried out using a 1:1 variation with a maximum of 3 repetitions, which consistently showed total conversion to methyl ester. Catalyst used was then characterized using FTIR, XRD, and XRF instruments, with the analysis results confirming that it was geopolymer-ZnO. Methyl ester obtained was analyzed using GC-MS, and the findings showed that the main compositions included methyl oleate (47.35%) and methyl palmitate (40.13%).